2020
DOI: 10.25259/cjhs_9_2019
|View full text |Cite
|
Sign up to set email alerts
|

Requesting physicians’ knowledge of X-radiation exposure from computed tomography scan examinations: A case study of two Nigerian tertiary hospitals

Abstract: Objective: Physicians who often request for computed tomography (CT) scan examinations are expected to have sound knowledge of radiation exposure (risks) to patients in line with the basic radiation protection principles according to the International Commission on Radiological Protection (ICRP), the Protection of Persons Undergoing Medical Exposure or Treatment (POPUMET), and the Ionizing Radiation (Medical Exposure) Regulations (IR(ME)R). The aim is to assess the level of requesting physicians’ knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Babaloui et al (2018) claimed that work experience correlates with radiation awareness and that nurses with higher work experience reflect more knowledge of radiation hazards. Contrastingly, the study was conducted with nurses from different wards that reported low radiation awareness that threatens both nurses' and patients' safety [24,25]. Therefore, educating health practitioners on radiation best practices is a crucial step in optimizing safe radiation practices [4].…”
Section: Discussionmentioning
confidence: 99%
“…Babaloui et al (2018) claimed that work experience correlates with radiation awareness and that nurses with higher work experience reflect more knowledge of radiation hazards. Contrastingly, the study was conducted with nurses from different wards that reported low radiation awareness that threatens both nurses' and patients' safety [24,25]. Therefore, educating health practitioners on radiation best practices is a crucial step in optimizing safe radiation practices [4].…”
Section: Discussionmentioning
confidence: 99%